Assessment of wind power generation impact on the distance protection operation; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Ruban N. Yu. Nikolay Yurievich; Askarov A. B. Alisher Bakhramzhonovich; Kievets A. V. Anton Vladimirovich; Rudnik V. E. Vladimir Evgenevich (2021, 2021)
Title screen